The Length and Semantic Structure of Article Titles—Evolving Disciplinary Practices and Correlations with Impact - Milojević, Staša (Frontiers in Research Metrics and Analytics, 2017)
In this paper we examine the characteristics of titles (average length, proportion of titles with subtitles, proportion of interrogatory and indicative titles) and how they changed over a substantial period of time (half a century). We consistently analyze core literature in five diverse fields, in order to probe the usage of titles as a disciplinary identity building tool. In addition, we study whether different types of titles are used differently by authors depending on their academic age and productivity and collaboration levels, which has not been studied before. Finally, we revisit the connection between title characteristics and impact. We found that belonging to some discipline is the strongest determinant for the length of the titles and the occurrence of different forms of titles. This suggests that authors try to comply with the norms set in their fields. However, these norms are not fixed in time. Over the decades, the practices have changed, some of them quite abruptly. Individual groups of authors most often did not differ in their practices regarding the use of titles. We find that using titles posed as questions or titles stating the result results in no citation benefit.